Formative evaluation based on monitoring of students ' INDIVAL achievements at the school: In the modern world, education is one of the most important factors contributing to the development of personality in order to prepare it for social life and productive work. - Sherzod, Pardayev (Журнал математики и информатики, 2024)
Abstract: In the modern world, education is one of the most important factors contributing to the development of personality in order to prepare it for social life and productive work. One of the tasks of school education is to update the problems of the quality of education, in general, and the quality of educational achievements, in particular. A structural element of the pedagogical system, aimed at implementing the feedback function in the educational process, is the assessment of individual educational achievements of schoolchildren. Therefore, in the context of updating educational structures, the task of searching for such approaches and means that can allow, by assessing the knowledge, abilities, and skills of schoolchildren pursuing their personal educational trajectory, to ensure the quality of individual educational achievements, becomes urgent. The article highlights the theoretical, methodological and didactic aspects of formative assessment from the perspective of foreign and domestic pedagogical science and practice.